Fashion Supply Chain Management - DM282 - 202301 - Ortega Meneses De Pichling, Mariela Beatriz (2023)
This subject is a specialty course in the career of Design and Management in Fashion, of a theoretical-practical nature aimed at students of the ninth cycle. This articulates the general competence of Innovative Thinking and the specific competence of Strategic Management. To be successful in the fashion world, it is required to efficiently plan, operate and manage the national and international supply chain effectively, control goods and economic resources. Participating in the business process of a fashion brand, having the knowledge and management of the tools for the management of the supply market in a changing business environment and security to address the challenges that arise in procurement management and throughout the chain are fundamental for good operability and decision making in different scenarios, that generate profitability and achieve recognition not only nationally but at the level of the best in the world. Through the course the student will understand the management of the supply chain, in its planning, processes and results applied to the design, commercial or production area where it is professionally involved. La presente asignatura es un curso de especialidad en la carrera de Diseño y Gestión en Moda, de carácter teórico-práctico dirigido a los estudiantes del noveno ciclo. En este se articula la competencia general Pensamiento Innovador y la competencia específica de Gestión Estratégica. Para ser exitoso en el mundo de la moda, se requiere planificar, operar y gestionar con eficiencia la cadena de suministro nacional e internacional de manera efectiva, controlar los bienes y recursos económicos. Participar del proceso de negocio de una marca de moda, tener el conocimiento y manejo de las herramientas para la gestión del mercado de suministro en un entorno empresarial cambiante y la seguridad para abordar los desafíos que se presentan en la gestión de adquisiciones y en toda la cadena son fundamentales para la buena operatividad y toma de decisiones ante diferentes escenarios, que generen rentabilidad y se logre el reconocimiento no solo nacional sino a nivel de los mejores en el mundo. A través del curso el estudiante comprenderá la gestión de la cadena de suministro, en su planificación, 1procesos y resultados aplicados al área de diseño, comercial o de producción donde se envuelva profesionalmente.